DE BENTINHO A CASMURRO: IDENTIDADES MÚLTIPLAS E MASCULINIDADES DESLIZANTES - Freitas, Débora Maia de (2015)
The problematization of the masculinity in the field of Humanities and Social Sciences is quite recent. Differently from what happened with women and feminilities, which have become an object of study since the 1970s and gained visibility in the 1980s with the adoption of a gender perspective, men and masculinities have turned into research object, only in the mid-1990s. Apprehend the factors that underlie the masculinity formation becomes relevant as they can put into question the stereotypes constructed about the male which are responsible for perpetuating sexist and oppressive practices and speeches. With this proposed work, which will be guided by the Cultural Studies and Gender Studies, and resort to theoreticians like Elisabeth Badinter, R. W. Connell e Michael Kimmel, we intend to bring out the timely debate about the male identity formation and masculinities that comprise it.To this end, we refer to the identity construction analysis of Bento Santiago, character in the book Dom Casmurro, written by Machado de Assis. Although Bento Santiago is the protagonist and the storyteller, for a long time he was overshadowed by the brightness and acumen of his enigmatic wife Capitu, which has always occupied a prominent position in academic research. Nevertheless sensitivity, passivity and naivety of the passionate teenager that, over the years, turned into coldness, apathy and bitterness, caught our attention and sparked our interest in the study of identity characteristics of Dom Casmurro`s storyteller. Bento Santiago, during the narrative, rebuild his trajectory and thus exposes to the reader and to himself his multiple identities, fragmented and unstable, that sometimes are contrary to the prevailing standard masculinity in his time. Our study will focus on these masculinities building, as well as the identity oscillations faced by the character during the long process of metamorphosis that transformed Bento into Dom Casmurro.